Prediction of Pulmonary Hypertension in Patients with Diffuse Parenchymal Lung Disease using Forced Vital Capacity/ Diffusion Capacity of Lung using Carbon Monoxide Ratio: A Cross-sectional Study - Anubhab Moulik; Jaydip Deb; Sourindra Nath Banerjee; Priyanka Ray; Pulak Kumar Jana; Sukanta Kodali; Saswata Ghosh (Journal of Clinical and Diagnostic Research)
Introduction: Diffuse Parenchymal Lung Disease (DPLD) comprise a heterogeneous group of diseases that occur when an abnormal healing response is induced by injury to the lungs. The diagnosis of DPLD is based on clinical presentation and radiological features. The initial diagnostic work-up includes Pulmonary Function Tests (PFT), such as spirometry and diffusion tests. Aim: To evaluate the accuracy of the Forced Vital Capacity/Diffusion Capacity of Lung for Carbon Monoxide (FVC/DLCO) ratio in predicting the presence of pulmonary hypertension in patients with DPLD. Materials and Methods: A cross-sectional study was conducted from January 2023 to March 2024 in the Inpatient Department (IPD) and Outpatient Department (OPD) of Nilratan Sircar (NRS) Medical College and Hospital, Kolkata, West Bengal, India. A total of 50 patients underwent High-Resolution Computed Tomography (HRCT) thorax and spirometry with DLCO, along with some other ancillary investigations. The parameters evaluated primarily include a descriptive account of the spirometry values, which were Forced Expiratory Volume in 1 second (FEV1), FVC and DLCO, as well as the 6-Minute Walk Distance (6MWD) for physiological assessment and ECHO 2D for the evaluation of pulmonary hypertension. Simple logistic regression was performed between the FVC/DLCO ratio and the presence or absence of pulmonary hypertension based on ECHO 2D with Doppler as the binary outcome. The Receiver Operating Characteristic (ROC) curve was obtained and the FVC/DLCO cut-off ratio was adjusted to achieve the highest sensitivity for predicting pulmonary hypertension based on this dataset. Results: Out of 50 patients (30 females and 20 males), the most common HRCT thorax pattern was Usual Interstitial Pneumonia (UIP), observed in 19 patients (38%), followed by Non Specific Interstitial Pneumonia (NSIP) in 11 patients (22%). The single most common DPLD was Idiopathic Pulmonary Fibrosis (IPF), with 11 patients (22%), while the most common group was Connective Tissue Disease-related DPLD (CTD-DPLD), comprising 22 patients (44%). An FVC/DLCO ratio of 0.97 was found to have a sensitivity of 81%, specificity of 77%, a Positive Predictive Value (PPV) of 86%, a Negative Predictive Value (NPV) of 70% and a diagnostic accuracy of 80% in predicting pulmonary hypertension. Conclusion: The FVC/DLCO ratio of 0.97 represents a modality that could aid in the diagnosis of pulmonary hypertension.